2008
DOI: 10.1063/1.2973819
|View full text |Cite
|
Sign up to set email alerts
|

Taylor dispersion in polymerase chain reaction in a microchannel

Abstract: Polymerase chain reaction ͑PCR͒ is commonly used for a wide range of DNA applications such as disease detection, genetic fingerprinting, and paternity testing. The importance of PCR has led to an increased interest in performing PCR in a microfluidic platform with a high throughput while using very small DNA quantities. In this paper we solve convection-diffusion equations for the DNA and deoxynucleoside triphosphate ͑dNTP͒ under conditions suitable for PCR operation in a microchip. These include pressure driv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…The dashed black line is a fit to (2Dt) 1/2 with D ¼ 1.7 Â 10 À9 m 2 s À1 , 5 times larger than the value given in TableI. This, however, is in good agreement with the Taylor dispersion theory,19,20 since P e x 15.…”
supporting
confidence: 65%
See 1 more Smart Citation
“…The dashed black line is a fit to (2Dt) 1/2 with D ¼ 1.7 Â 10 À9 m 2 s À1 , 5 times larger than the value given in TableI. This, however, is in good agreement with the Taylor dispersion theory,19,20 since P e x 15.…”
supporting
confidence: 65%
“…4(c) (1.7 × 10 −9 m 2 s −1 ) indicating a quantitative discrepancy between the experimental data and our model. We suspect that this is due to some accelerated diffusion mechanism occurring at the front, such as Taylor dispersion [16,17]. To resolve this issue, experiments of higher accuracy are required as well as direct tracking of the sugar without using a dye.…”
Section: B Corrections To the Equation Of Motionmentioning
confidence: 99%
“…[15] studied the thermal performance of the continuous flow PCR chip by taking temperature non-uniformity and deviations from the target temperatures in different reaction zones as the evaluating parameters. Lee et al (2008) [16] numerically studied the Taylor dispersion effect on a droplet-based PCR system. The results indicated that due to the dispersion of the nucleotide inside the microchannel caused by the flowing, complete depletion of dNTPs at certain axial location along the microchannel may be generated and leads to an unexpected termination of DNA amplification.…”
Section: Introductionmentioning
confidence: 99%
“…Since the pioneering work of Taylor this problem has been extended to cover more complicated settings including various geometrical complexities, 24,25 oscillating flows, 7,26 transient phenomena, 19 effects of chemical reactions, [27][28][29] and many others (see, for instance, books 1, 2 and recent papers 19,21 ). An important generalization of the problem is to account for the "effect of wall" (absorption and desorption, as well as diffusion of the particle on the wall).…”
Section: Introductionmentioning
confidence: 99%